An Exploration of Enterprise ESG Practice Paths Based on Fintech Innovation - Mo, Zekai (Scientific Journal of Technology, 2025)
With the deepening global adoption of sustainable development, environmental, social, and governance (ESG) considerations have become core dimensions for measuring a company’s overall value. The rapid evolution of Fintech offers new avenues for companies to overcome bottlenecks in ESG practice. This article explores the inherent connection between Fintech innovation and corporate ESG practices. Through literature analysis and logical deduction, it identifies pain points in corporate ESG practices, such as irregular data collection, opaque information disclosure, and inefficient performance evaluation. The article then analyzes these issues from the perspectives of technology, implementation, and risk. The study finds that Fintech tools such as big data, blockchain, and artificial intelligence can play a key role in ESG data integration, credible disclosure, and intelligent assessment, respectively. Companies must integrate Fintech into the entire ESG governance process through a comprehensive approach of "technology adaptation - architecture optimization - collaborative collaboration." At the same time, they must mitigate risks such as data security and insufficient technological adaptability. This article aims to provide theoretical guidance for companies leveraging Fintech to improve the quality of their ESG practices, helping them achieve the dual goals of sustainable development and value enhancement.